2017
DOI: 10.1080/19440049.2017.1292558
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated solvent extraction by using an ‘in-line’ clean-up approach for multiresidue analysis of pesticides in organic honey

Abstract: The worldwide loss of honeybee colonies may be due to their exposure to several contaminants (i.e., pesticides); such contamination may also have impacts on consumers' health. Therefore, it is essential to develop quick and new methods to detect several pesticide residues in honey samples. In this study, the effectiveness of accelerated solvent extraction (ASE) was compared with QuEChERS methods for the analysis of 53 pesticides in organic honey by gas chromatography-triple quadrupole mass spectrometry. Two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The Full Evaporative Technique (FET), which is popular within the cannabis testing industry, was not evaluated in the current study as this technique’s foundation is HS-Syringe; and the results discussed in HS-Syringe vs. HS-SPME Arrow vs. DI-SPME Arrow demonstrated that HS-Syringe did not perform as well as HS-SPME Arrow, which was also inferior to DI-SPME Arrow for the analysis of terpenes. Other industries already capitalize on the benefits of ASE 350 ( Ligor et al, 2014 ; Chiesa et al, 2017 ; Hu et al, 2020 ; Ning et al, 2020 ). Therefore, a simple hand shakeout solvent extraction method was compared to an ASE 350 extraction method to evaluate the performance of each technique for extracting terpenes from cannabis flower.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Full Evaporative Technique (FET), which is popular within the cannabis testing industry, was not evaluated in the current study as this technique’s foundation is HS-Syringe; and the results discussed in HS-Syringe vs. HS-SPME Arrow vs. DI-SPME Arrow demonstrated that HS-Syringe did not perform as well as HS-SPME Arrow, which was also inferior to DI-SPME Arrow for the analysis of terpenes. Other industries already capitalize on the benefits of ASE 350 ( Ligor et al, 2014 ; Chiesa et al, 2017 ; Hu et al, 2020 ; Ning et al, 2020 ). Therefore, a simple hand shakeout solvent extraction method was compared to an ASE 350 extraction method to evaluate the performance of each technique for extracting terpenes from cannabis flower.…”
Section: Resultsmentioning
confidence: 99%
“…The following study was conducted to evaluate more modern sample preparation and introduction techniques and demonstrate their potential value to cannabis compliance testing laboratories in need of guidance for qualitative and quantitative terpenes analysis. In addition, this study evaluated accelerated solvent extraction (ASE 350) of terpenes in cannabis samples, which is commonly used in other markets within the analytical testing industry ( Ligor et al, 2014 ; Chiesa et al, 2017 ; Hu et al, 2020 ; Ning et al, 2020 ). Furthermore, to avoid potentially inaccurate reporting, matrix matched standards were used for calibration.…”
Section: Introductionmentioning
confidence: 99%
“…These environmentally green tools even allow the coupling with in-line clean-up steps using adsorbents. This strategy was followed for the extraction of pesticides from honey that were subsequently analyzed by GC-MS/MS [5]. Readers interested on gaining deeper insight on extraction methods and sample preparation for the analysis of contaminants in foods are referred to recent excellent review papers [2,[6][7][8][9][10][11][12].…”
Section: Detection Of Chemical Contaminants: Food Production-relatedmentioning
confidence: 99%
“…In the case of honey, the nature of the matrix makes extraction of pesticides a complicated process because of the high sugar content and the presence of other compounds such as proteins, amino acids, and organic acids. These groups of chemicals may interfere with target pesticides during the analysis [18,19]. Pesticides in honey are commonly extracted using pressurized liquid extraction [18], the QuEChERS method [13,16,19], liquid-liquid extraction (LLE) [14,15,18,20], or by SPE after dilution of the honey sample with water [20].…”
Section: Introductionmentioning
confidence: 99%
“…These groups of chemicals may interfere with target pesticides during the analysis [18,19]. Pesticides in honey are commonly extracted using pressurized liquid extraction [18], the QuEChERS method [13,16,19], liquid-liquid extraction (LLE) [14,15,18,20], or by SPE after dilution of the honey sample with water [20]. Furthermore, dispersive liquidliquid microextraction (DLLME) [8,9] was also used for the analysis of pesticides residue in honey samples.…”
Section: Introductionmentioning
confidence: 99%